2018
DOI: 10.4103/aer.aer_111_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous bolus and infusion of dexmedetomidine on characteristics of subarachnoid block

Abstract: Aims:Dexmedetomidine is very dynamic drug, used for analgesia, sedation, blunting the laryngoscopic responses and as adjuvants in regional anesthesia. Studies have shown that intravenous (iv) dexmedetomidine given during spinal anesthesia increases the quality of subarachnoid block (SAB). In this study, we compare the two iv regimen of dexmedetomidine on analgesic effect of spinal anesthesia. One is bolus dose of dexmedetomidine and other is infusion during the surgery, both given after induction of spinal ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Recently, dexmedetomidine has been commonly applied as an assistant drug for a subarachnoid block during the perioperative period. [37][38][39] A previous meta-analysis by Liu et al 15 considered that the addition of dexmedetomidine could significantly reduce the onset time of spinal anesthesia. However, two trials 14,20 in that metaanalysis did not meet the inclusion criteria because of the combined spinal and epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, dexmedetomidine has been commonly applied as an assistant drug for a subarachnoid block during the perioperative period. [37][38][39] A previous meta-analysis by Liu et al 15 considered that the addition of dexmedetomidine could significantly reduce the onset time of spinal anesthesia. However, two trials 14,20 in that metaanalysis did not meet the inclusion criteria because of the combined spinal and epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dexmedetomidine has been commonly applied as an assistant drug for a subarachnoid block during the perioperative period. 3739 A previous meta-analysis by Liu et al. 15 considered that the addition of dexmedetomidine could significantly reduce the onset time of spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Which was statistically significant(P<0.001). Vatsalya et al 16 & Zhang H et al 17 concluded that administration of IV dexmedetomidine during subarachnoid block hastens onset of sensory & motor block. We observed statistically significant difference in duration of sensory block & prolongation in duration of motor blockage & time for two segment regression between group D & M (P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies, including one meta-analysis, have reported the effects of intravenous dexmedetomidine (Dex) on subarachnoid block [2][3][4][5][6][7][8][9][10][11][12][13]. While some of the studies analyzed the effects of intravenous Dex by administering it first as a bolus followed by infusion [2][3][4][5][6][7], other studies analyzed it as either a bolus only [8][9][10] or as a continuous infusion only [12].…”
Section: Introductionmentioning
confidence: 99%
“…While some of the studies analyzed the effects of intravenous Dex by administering it first as a bolus followed by infusion [2][3][4][5][6][7], other studies analyzed it as either a bolus only [8][9][10] or as a continuous infusion only [12]. Besides, one study compared the bolus dose versus the infusion of Dex to evaluate the effects on the subarachnoid block [13].…”
Section: Introductionmentioning
confidence: 99%